Petrologia do magmatismo tardi-brasiliano no Maciço São José de Campestre(RN/PB), com ênfase no Plúton Alcalino Caxexa - Nascimento, Marcos Antonio Leite do (2000)
The area studied is located on the north-easternmost portion of the Borborema Province, on the so-called São José de Campestre Massif, States of RN and PB, Northeast Brazil. Field relations and petrographic, geochemical and isotope data permitted the separation of five suites of plutonic rocks: alkali-feldspar granite (Caxexa Pluton), which constitutes the main subject of this dissertation, amphibole-biotite granite (Cabeçudo Pluton), biotite microgranite, gabbronorite to monzonite (Basic to Intermediate Suite) and aluminous granitoid. The Caxexa Pluton is laterally associated to the Remígio Pocinhos Shear Zone, with its emplacement along the mylonitic contact between the gneissic basement and the micashists. This pluton corresponds to a syntectonic intrusion elongated in the N-S direction, with about 50 km2 of outcropping surface. It is composed exclusively of alkali-feldspar granites, having clinopyroxene (aegirine-augite and hedenbergite), andradite-rich garnet, sphene and magnetite. It is classified geochemically as high silica rocks (>70 % wt), metaluminous to slightly peraluminous (normative corindon < 1%), with high total alkalis (>10% wt), Sr, iron number (#Fe=90-98) and agpaitic index (0.86-1.00), and positive europium anomaly. The Cabeçudo Pluton is composed of porphyritic rocks, commonly containing basic to intermediate magmatic enclaves often with mingling and mixing textures. Petrographically, it presents k-feldspar and plagioclase phenocrysts as the essential minerals, besides the accessories amphibole, biotite, sphene and magnetite. It is metaluminous and shows characteristics transitional between the calc-alkaline and alkaline series (or monzonitic subalkaline). Its REE content is greater than those ones of the Caxexa Pluton and biotite microgranite, and all spectra have negative europium anomalies. The biotite microgranites occur mainly on the central and eastern portion of the mapped area, as dykes and sheets with decimetric thickness, hosted principally in orthogneisses and micashists. Their field relationships as regards the Caxexa and Cabeçudo plutons suggested that they are late-tectonic intrusions. They are typically biotite granites, having also sphene, amphibole, allanite, opaques and zircon in the accessory assemblage. Geochemically they can be distinguished from the porphyritic types because the biotite microgranites are more evolved, peraluminous, and have more fractionated REE spectra. The Basic to Intermediate rocks form a volumetrically expressive elliptical, kilometric scale body on the Southeast, as well as sheets in micashists. They are classified as gabbronorites to monzonites, with the two pyroxenes and biotite, besides subordinated amounts of amphibole, sphene, ilmenite and allanite. These rocks do not show a well-defined geochemical trend, however they may possibly represent a monzonitic (shoshonitic) series. Their REE spectra have negative europium anomalies and REE contents greater than the other suites. The aluminous granitoids are volumetrically restricted, and have been observed in close association with migmatised micashists bordering the gabbronorite pluton. They are composed of almandine-rich garnet, andalusite, biotite and muscovite, and are akin to the peraluminous suites. Rb-Sr (whole rock) and Sm-Nd (whole-rock and mineral) isotopes furnished a minimum estimate of the crystallization (578±14 Ma) and the final resetting age of the Rb-Sr system (536±4 Ma) in the Caxexa Pluton. The aluminous granitoid has a Sm-Nd garnet age similar to that one of the Caxexa Pluton, that is 574±67 Ma. The strong interaction of shear bands and pegmatite dykes favoured the opening of the Rb-Sr system for the Caxexa Pluton and biotite microgranite. The amphibole-plagioclase geothermometer and the Al-in amphibole geobarometer indicate minimum conditions of 560°C and 7 kbar for the Cabeçudo Pluton, 730°C and 6 kbar for the microgranite and 743°C and 5 kbar for the basic to intermediate suite. The Zr saturation geothermometer reveals temperatures of respectively 855°C, 812°C and 957°C for those suites, whereas the Caxexa Pluton shows temperatures of around 757°C. The Caxexa, Cabeçudo and microgranites suites crystallized under high fO2 (presence of magnetite). On the other hand, the occurrence of ilmenite suggests less oxidant conditions in the basic to intermediate suite. Field relations demonstrate the intrusive character of the granitoids into a tectonically relatively stable continental crust. This is corroborated by petrographic and geochemical data, which suggest a late- or post-collisional tectonic context. It follows that the generation and emplacement of those granitoid suites is related to the latest events of the Brasiliano orogeny. Finally, the relationships between eNd (600 Ma), TDM (Nd) and initial Sr isotope ratio (ISr) do not permit to define the precise sources of the granitoids. Nevertheless, trace element modelling and isotopic comparisons suggest the participation of the metasomatised mantle in the generation of these suites, probably modified by different degrees of crustal contamination. In this way, a metasomatised mantle would not be a particular characteristic of the Neoproterozoic lithosphere, but a remarkable feature of this portion of the Borborema Province since Archaean and Paleoproterozoic times.